Determination of Location Using RSSI and LQJ based on Fuzzy Logic - Tuncer, Sevil; Tuncer, Taner (Ieee, 2015)
Sensor location estimation is an important problem in wireless sensor networks. GPS can be used to obtain location information. GPS systems are not ideal for many applications due to their excessive power consumption and high cost. As an alternative to GPS, Sensor location can be estimated through the usage of at least 3 nodes with known locations. Received Signal Strength Indication (RSSI) is the simplest and most inexpensive technique used to determine distance and location, and is a standard feature on every sensor. But, only the use of RSSI is not accurate. In addition to the RSSI parameter, LQI is used too. However, RSSI can be affected by noise and environmental obstacles Kablosuz agin konumlandirildigi ortam homojen bir yapiya sahip olmadigmdan. For this reason, it is difficult to set up a mathematical model for RSSI. this paper present a method based on fuzzy logic to estimate the location of a sensor of unknown location. Estimate location simulation was made in Matlab and obtained results were compared with centroid localization method.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: RSSI; LQI; Centroid Localization Method